Chapter Did Peter van Selow (1582-1650) have Dutch roots? New sources about a well-known type founder and printer - Maier, Ingrid (Amsterdam University Press, 2022)
Previous attempts to describe the life of Peter van Selow, one of the more important type founders and printers in Sweden during the first half of the seventeenth century, have suffered from serious deficiencies: we knew neither the dates of his birth and death, nor was it clear where he was born. Quite consistently he was characterised as a Dutchman. Thanks to a newly discovered funeral sermon that has survived in Stuttgart, many blank spots in Van Selow's biography can now be filled in: Van Selow was born in Grevesmühlen in Mecklenburg, 1582, and he died in Stockholm, 1650. This study combines information from the recently located new source with long-known Swedish scholarship on the hitherto enigmatic type founder and printer. Sources about the Danish astronomer Tycho Brahe, in whose service Van Selow was employed for several years, were also used to fill in some gaps.